Coat Protein Gene based Characterization of Cucumber Mosaic Virus Isolates Infecting Banana in India - Bushra Aquil, Qazi Mohd. Rizwanul Haq*, Shahanavaj Khan, Arif Tasleem Jan, (Journal of Phytology, 2011)
Banana plants showing typical yellow stripes on leaves as symptoms, in addition to leaf distortion and stunting of plant were collected from Karnataka (KAR), Maharashtra (MH) and Uttar Pradesh (UP) in India. The causal agent was identified as Cucumber mosaic virus (CMV) on the basis of transmission electron microscopy and reverse transcription polymerase chain reaction (RT-PCR). Complete coat protein (CP) gene of all isolates were amplified using gene specific primers for coat protein (CP), followed by cloning into desired cloning vector for sequencing. Sequenced region were found containing complete single open reading frame of 657 nucleotides, potentially coding 219 amino acids. Sequence analysis of CP gene showed 93%-98% (at nucleotide) and 94%-99% (at amino acid) sequence identity between all three Indian isolates. On comparing CP gene sequences of CMV KAR, CMV MH and CMV UP with CMV P isolate (Physalis minima); we got 94%, 99% and 96% identity respectively. High degree identity at nucleotide level between these isolates of banana and Physalis minima (a weed) suggest that Physalis minima could be an alternate host of CMV banana. Phylogenetic analysis of nucleotide along with amino acid sequence of coat protein gene revealed that all our isolates belong to IB subgroup.Ã‚Â  In short, it appears that there occurs a high incidence of CMV infecting banana belonging to IB subgroup in most parts of Indian subcontinent. Key words: Banana, CMV, CP gene, RT-PCR